The Clarification of Noble Character - Umar bin Hafiz, Al-Habib. (South Africa.: : DTI publishinng House, 2014)
If Allah wishes to bestow His grace upon someone, He places in their heart the desire to travel the path towards self-purification and gives them the ability to rectify the attributes of their soul. Allah decreed that success in this life and the next be judged according to the degree to which people purify their souls and attain noble character. It is thus the duty of every believer to seek to attain noble character and emulate their Prophet SAW who said: I was only sent to perfect noble character. In a series of thirty lessons, al-?abib ?Umar bin ?afi? discusses the importance of character refinement and focuses on the traits and qualities that every believer should strive to acquire. He demonstrates how the Prophet SAW and the pious people of his nation embody each character trait and shows the reader how to emulate them. In our times we have never been more in need of improving our character and rectifying ourselves. This is a book for every seeker, every believer and every family. May it be a source of light for every heart and the catalyst for moral transformation.